The aggregate effects of labor market frictions. Issue 3 (24th July 2019) - Elsby, Michael W. L.; Michaels, Ryan; Ratner, David
Abstract : Labor market frictions are able to induce sluggish aggregate employment dynamics. However, these frictions have strong implications for the source of this propagation: they distort the path of aggregate employment by impeding the flow of labor across firms. For a canonical class of frictions, we show how observable measures of such flows can be used to assess the effect of frictions on aggregate employment dynamics. Application of this approach to establishment microdata for the United States reveals that the empirical flow of labor across firms deviates markedly from the predictions of canonical labor market frictions. Despite their ability to induce persistence in aggregate employment, firm‐size flows in these models are predicted to respond aggressively to aggregate shocks, but react sluggishly in the data. The paper therefore concludes that the propagation mechanism embodied in standard models of labor market frictions fails to account for the sources of observed employment dynamics.